Concordance between Axillary Ultrasound and Sentinel Biopsy in Clinically Node-Negative Early Breast Cancer - Afroz Mushtaq; Ali Ayesha Khan; Razia Bano; Syeda Rifaat Qamar Naqvi; Shabnum Nawaz; Fahad Ali Khan; Sana Mushtaq; Palwasha Khan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the sensitivity of axillary ultrasound in detecting axillary nodal metastasis in clinically and radiologically uninvolved axillary nodes in early carcinoma breast by comparing with sentinel node biopsy histopathology on frozen section.